PERFORMANCE ANALYSIS VILLAGE FAMILY PLANNING ADMINISTRATOR (PPKBD) IN KADING VILLAGE, TANETE RIAJA SUB-DISTRICT BARRU DISTRICT - Dian Pratiwi; Asriani Asriani; Halijah Halijah (Jurnal Scientia, 2023)
This study aims to determine the performance of village family planning assistants (PPKBD) and to determine the factors that influence performance (PPKBD) in Kading Village, Tanete Riaja District, Barru Regency. The research method used is descriptive qualitative research method, the data sources are primary data and secondary data. Data collection techniques were obtained by means of observation, interviews and documentation. As well as data analysis techniques include the stages of data collection, data reduction, data presentation and drawing conclusions.The results showed that the performance of the Village Family Planning Assistant (PPKBD) in Kading Village, Tanete Riaja District, Barru Regency was categorized as quite good. It is based on data analysis through research indicators are motivation, ability and opportunity. Factors Affecting the Performance of Village Family Planning Assistants (PPKBD) in Kading Village, Tanete Riaja District, Barru Regency are motivation, job satisfaction, stress level, working conditions, compensation system and job design.